Environmental Management in Germany - Szymańska-Brałkowska, Małgorzata (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2010)
The article raises the problem of environmental management in Germany. Its main research field is focused on environmental management systems (EMS) certified according to ISO 14001 and on Ecology Management and Audit Scheme – EMAS. The main target of this paper is to analyse how EMS operate in the German economy and to evaluate the role of ecological initiatives among companies dealing with various aspects of global economic and environmental issues. The article underlines Germany’s strong economic performance that leads to generating approximately 20% of EU’s GDP . This makes the German economy one of the strongest among the EU Member States. The research shows that the environmental management plays an important role for German companies and organisations. The high rate of ISO 14001 implementations (4,877 in the end of 2007) gives Germany the fourth rank in Europe and eight place globally. The evaluation of companies that took part in EMAS and shows Germany as a leading country in this research field (1,417 companies and organisations in 2009). The analysis carried out in this research underlines the high importance of environmental management in the German economy and on the company level. Moreover, it shows the increasing significance of environmental CSR as a way of competing on a global market, improving company’s image and fitting to global economic and environmental demand. Improving company’s environmental performance by implementation of environmental management leads to costs reduction and rationalisation of its organisation. Therefore, it is an appropriate way of dealing with the current global economic crisis and environmental issues.